2010
DOI: 10.3138/physio.62.2.155
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Weekend Physiotherapy Services in Three Tertiary Hospitals in the Greater Toronto Area

Abstract: Purpose: The aims of this study were (1) to describe the cardiorespiratory physiotherapy weekend service (PWS) at three tertiary hospitals in the Greater Toronto Area (GTA) and (2) to compare measures of staff burden among the clinical service areas in one of the hospitals that had a programme-based management structure. Method: Two focus-group meetings were held with physiotherapists from hospitals within the GTA. Thereafter, variables characterizing the PWS were collected over 8 months, using a standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Less consistency in PT and OT staffing is reported to be associated with therapist difficulties with patient populations due to having limited or no expertise. 2223 Distributing PT and OT staff with compatible expertise into clustered service areas (e.g., surgical ICU and surgical stepdown) may reduce variance in care as well as improve familiarity and interprofessional experiences amongst the different ICU providers. 2223 …”
Section: Discussionmentioning
confidence: 99%
“…Less consistency in PT and OT staffing is reported to be associated with therapist difficulties with patient populations due to having limited or no expertise. 2223 Distributing PT and OT staff with compatible expertise into clustered service areas (e.g., surgical ICU and surgical stepdown) may reduce variance in care as well as improve familiarity and interprofessional experiences amongst the different ICU providers. 2223 …”
Section: Discussionmentioning
confidence: 99%
“…14 Recently, a prospective workload assessment of physiotherapists working on weekends was conducted in three Toronto-area tertiary-care hospitals. 15 The authors found variation among these hospitals in terms of weekend and evening PT service delivery, the ability of physiotherapists working on weekends to share the workload, and the proportion of physical therapists completing unpaid overtime. This variation appeared to be related to the institutions' management structures (departmental vs. programme management).…”
mentioning
confidence: 99%
“…This variation appeared to be related to the institutions' management structures (departmental vs. programme management). 15 A survey of tertiarycare hospitals across Canada 16 found a 10% higher rate of provision of WPT than a survey of a broader range of hospital types performed a decade earlier. 14 Since earlier findings suggest that differences in access to weekend and evening service delivery are likely between academic and non-academic facilities, 13,14 investigations into facilities outside the tertiary setting should be conducted.…”
mentioning
confidence: 99%
“…Patients requiring around-the-clock physiotherapy often, but not always, have acute or subacute respiratory conditions; 5 these can rapidly alter a patient's clinical status and often require intensive physiotherapy, necessitating several treatments per day and sometimes treatment at night. 8,9 The availability of 24/7 cardiorespiratory physiotherapy allows therapy to be started early, thereby avoiding the need to wait until the next morning or after the weekend and thus potentially improving patient care and outcomes.…”
Section: Discussionmentioning
confidence: 99%